INCLUSIVE EDUCATION FOR DOWN SYNDROME STUDENT: NARRATIVE STUDY AT BRAWIJAYA UNIVERSITY - Abdul Rohman; Abd. Rahman Ambo' Dalle (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2022)
Abstract: Inclusive Education for Down syndrome Student: Narrative Study at Brawijaya University. This article aims to portray the role of PSLD as a study center for disability services at Brawijaya University in providing inclusive education. The method used in this article is qualitative research with a narrative approach. The results in this article include, firstly, PSLD volunteers are equipped with abilities that are by the needs of students and lecturers with disabilities as provisions for Down Syndrome students. Second, educational games are often used in the teaching and learning process, because they are considered the most effective in controlling the psychological condition of Down Syndrome students with the initials FI. Third, the patience of the FI's parents is also a crucial factor to facilitate externally FIs to complete their tasks optimally and completely